Systematic Literature Review : Increasing Mathematical problem-solving Ability Through the 7E Cycle Learning Model - Handayani , Lutfi; Waluya, Stevanus Budi (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Model Learning Cycle 7E has been proven effective in improving students' understanding of concepts. However, research regarding the role of models in Learning Cycle 7E In developing students' problem-solving abilities, still needs to be done in more depth. This research aims to develop a more comprehensive framework regarding how to model Learning Cycle 7E can be used to facilitate the development of students' problem-solving abilities. In this research, a review of research articles on problem-solving abilities in mathematics with models was carried out in Learning Cycle 7E. This research will identify the characteristics of effective learning in developing students' problem-solving abilities using the 7E model. Through analysis of 10 articles published from 2019 to 2024, which we found in the Crossref and Google Scholar databases using the Publish or Perish application. By using keywords or a combination of keywords.